Dietary protein: lipid ratio and lipid nature affects fatty acid absorption and metabolism in a teleost larva - Morais, S. (2018)
Studies with teleost larvae have reported poor performance associated with quantitative lipid imbalances in the diet. The present study examined the effect of dietary protein:neutral lipid ratio on fatty acid (FA) absorption efficiency and metabolism in larval Senegalese sole. In addition, the effect of lipid class (triolein (TRI) and L-3-phosphatidylcholine-1,2-di-oleoyl (PC)), carbon number and degree of saturation of the labelled NEFA, stearic acid (SA), oleic acid (OA) and DHA) was tested. FA absorption was determined by tube feeding [1-C-14]-labelled lipids and NEFA after a single meal of either non-enriched Artemia (NEA) or Artemia enriched on a soyabean oil emulsion (EA), or after feeding these diets over an extended period of time (18 d). The tested dietary protein:lipid ratios had no short-term influence but long-term feeding of a diet higher in neutral lipid (EA) increased lipid accumulation within the gut epithelium and resulted in lower FA absorption (higher label evacuation and lower retention of dietary FA), which may partially explain the trend for lower growth observed with this diet. The lipids and NEFA, showed different digestive and metabolic properties, independent of feeding regime. FA absorption increased with unsaturation, being lowest for SA, followed by OA, and highest for DHA. In addition, sole larvae had a lower capacity to digest and absorb FA esterified to TRI, compared with PC, with the order of decreasing absorption being NEFA > PC >> TRI. Moreover, larvae appeared to discriminate between the source of OA, as this FA in the free form or esterified to PC was catabolised less than TRI.